Overcoming Aspirin Resistance with Loading Clopidogrel Earlier in Elective Percutaneous Coronary Intervention - Ozcan, Ozgur Ulas; Tutar, Eralp; Candemir, Basar; Ustun, Elif Ezgi; Erol, Cetin (International Journal of Angiology, 2015)
We aimed to analyze the clinical effect of clopidogrel loading time on adverse cardiovascular events among patients with aspirin resistance. Recurrent adverse events may still occur despite dual antiplatelet therapy after coronary stenting. Aspirin resistance is one of the possible reasons of this trouble. Optimal antiplatelet strategy for coronary stenting is unknown among patients with aspirin resistance. A total of 980 patients scheduled for elective coronary stenting were enrolled and allocated into two groups according to the loading time of clopidogrel more or less than 6 hours before coronary intervention (early- or late-loaded groups, respectively). Aspirin resistance was determined according to the urinary levels of 11-dehydrothromboxane B2. Overall 240 patients who were allocated to early- and late-loaded groups were identified as aspirin resistant according to the urinary levels of 11-dehydrothromboxane B2. After a follow-up period of 12 months major adverse cardiac events were observed among 16 patients (13.9%) in the early-loaded group and 30 patients (25.8%) in the late-loaded group (p = 0.02). Early loading of clopidogrel was an independent predictor of lower rate of cardiac events (hazard ratio = 0.46 [0.32–0.76, 95% confidence interval], p = 0.001). The rates of bleeding events and periprocedural myocardial infarction were similar in early- and late-loaded groups. The current study demonstrated that loading of clopidogrel earlier than 6 hours before elective coronary stenting among aspirin-resistant patients was associated with increased benefits for ischemic events with similar bleeding rates.
Keywords: antiplatelet drugs; chronic stable angina; coronary artery disease; stents